Pemanfaatan lahan pekarangan dalam upaya menciptakan kemandirian pangan di Pesantren Tuhfathul Anfaniyah, Lombok Tengah - Dewi, Suprayanti Martia; Nufus, Novita Hidayatun; Jufri, Afifah Farida; Putri, Dwi Noorma; Ashari, Anjar Pranggawan; Jihadi, Amrul (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2024)
Yard land has the potential to be utilized as optimally as possible, one of which is by implementing simple plant cultivation. Service activities will be carried out from March to April 2023 at the Tuhfathul An-Fananiah foundation, Beber Village, Batukliang District, Central Lombok. Implementation began by conducting a field survey and coordinating activities with the management of the Tuhfathul An-Fananiah Islamic Boarding School. The targets of service activities are Plus Yasfa'an High School students. Several stages of activities include (1) preparation of planting media and types of yard plants that are appropriate to the surrounding environmental conditions (2) socialization of the use of yard land by cultivating plants in an effort to achieve food independence in the Islamic boarding school environment 3) Assistance with planting activities in the Islamic boarding school yard land. Socialization activities will be held on April 1 2023 in the foundation hall. Planting of yard plants will be carried out on May 5 2023 in the courtyard of the daughter's cottage so that maintenance can be carried out regularly. Activities went according to plan and obtained good results. The students have been given provisions in managing the land around the Islamic boarding school and this can be done sustainably by the next generation and residents of the Islamic boarding school environment.